INSTRUCTION TO OVERCOME THE DIFFICILTY IN ACQUIRING ENGLISH SEGMENTS NON EXISTENT IN KURDISH TO KURDISH EFL LEARNERS - I. NASER, LUREEN; M. HASAN, REJAN (Journal of Duhok University, 2017)
In every language, speakers usually have fixed numbers of sound-units which are combined together to form the words of the language. O’Connor (1980) describes this as having a number of fixed boxes for each sound, which we go to when we speak to form words. Every language has different numbers and arrangements of these boxes, which become stronger with time. As a result, when learners try to learn a new language which certainly has different numbers of boxes compared to their native language, they need to build up new boxes for the new sounds. Usually this is not a very easy thing to do unless they have enough exposure to the target language. So, when they find it difficult to build a new box, they replace these sounds with other sounds that are articulately closer to them. For example, they replace the sound /T/ with /s/ which are both voiceless fricatives and are very common in English. Dental fricatives in English are among the most mispronounced sounds by Kurdish EFL learners. Students will overcome this difficulty after instruction. The problem with these sounds can either be a perception problem or a production problem. Concerning the velar nasal, learners cannot easily articulate the sound /N/ because their organs of speech are not used to make the movements that produce this sound. Besides, they cannot hear the sound easily and often confuse it with this combination /ng/. For this reason, they lack the skill of predicting its presence or absence in a word. As for the dental fricatives /T/ and /D/, they are inherently difficult for production and articulation, not only for learners but also for native speakers.  The other difficulty of these sounds could be in their perception. Acoustically speaking, these sounds are perceptually weak and are easily confused with labio-dental fricatives /f/ or /v/ and can thus be perceptually ambiguous (Jekiel, 2012).It is hypothesized that Kurdish EFL learners will also face difficulty with these sounds. This difficulty can be overcome with appropriate instruction. Ten participants, who have not received prior instruction in English phonetics and phonology, were chosen for the purpose of the analysis. They were asked to read (15) minimal pairs of each target sound contrasted with similar sounds in a pre-instruction test. They were later asked to read them again in a post-instruction test. After examining the production of these target sounds in both tests, it appears that the number of mispronunciation errors is reduced from (84 %) to (14%) of the data. This reduction in the number of errors is the result of the given instruction. It appears that providing instruction is valuable and efficient in overcoming this difficulty.  The results are of value to the teachers who teach Phonetics and Phonology in the English departments. This also proves that teaching Phonetics and Phonology should not be underestimated.